What do incoming university students believe about open science practices in psychology? - Beaudry JL; Williams M; Philipp MC; Kothe EJ (SAGE Publications)
Background: Understanding students’ naive conceptions about the norms that guide scientific best practice is important so that teachers can adapt to students’ existing understandings. Objective: We examined what incoming undergraduate students of psychology believe about reproducibility and open science practices. Method: We conducted an online survey with participants who were about to start their first course in psychology at a university (N = 239). Results: When asked to indicate how a researcher should conduct her study, most students endorsed several open science practices. When asked to estimate the proportion of published psychological studies that follow various open science practices, participants’ estimates averaged near 50%. Only 18% of participants reported that they had heard the term “replication crisis.” Conclusion: Despite media attention about the replication crisis, few incoming psychology students in our sample were familiar with the term. The students were nevertheless in favour of most open science practices, although they overestimated the prevalence of some of these practices in psychology. Teaching Implications: Teachers of incoming psychology students should not assume pre-existing knowledge about open science or replicability.
Keywords: Open science; Psychology; Teaching; Reproducibility; Replication; 1302 Curriculum and Pedagogy; 1701 Psychology